Reykjavikurhöfn - Unbekannt (ETH-Bibliothek Zürich, Bildarchiv, 1907)
Frei zum Herunterladen : Botschaft der Postkarte: Reykjavik has now 10’000 inhabitants, but Iceland has altogether 80’000 inhabitants.he next summer we expect the danish King to Reykjavik with some of his ministers.e have now beginned to use our own flag. It is just like the danish flag, but lightblue where the danish one is red. The danish people do not like this spirit of liberty. Do you ever expect to travel to Iceland? Do you understand the Icelandic language?. Poststempel 6.2.1907